Living Hadis Tasyakuran Khatam Al-Qur’an di Yayasan Nuzhatul Muttaqien Tangerang - Arbi Nazhief Fauzan; Muhammad Alif; Masrukhin Muhsin (Al-Mu'tabar, 2024)
This study aims to explain how the tradition of Tasyakuran khataman Al-Qur'an in the community, especially in the Nuzhatul Muttaqien foundation. And also analyze what hadiths related to the tasyakuran khataman and the process of implementation, as well as analyzing the values contained therein such as religious values, friendship, charity and so on. This research uses a case study method, such as how the tasyakuran khatmil Qur'an is used in the community, as well as the hadith analysis method to find out the teachings of the Prophet about the appreciation of the Qur'an and its practice. The result is that each region's interpretation of the hadith reading is different, not fixed to just one feast. The most important thing is that the Muslim community can appreciate the Qur'an more because it is a gathering witnessed by thousands of angels and also the descent of Allah's Grace.